Ag / double-ligand Sn-MOF composite material as well as preparation method and application thereof
The Ag/dual-ligand Sn-MOF composite material addresses the low catalytic activity and light-dependent deactivation of photocatalysts by enhancing charge transfer and electron storage, ensuring effective degradation of organic pollutants in wastewater.
Patent Information
- Application Number
- CN202411672523.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Photocatalysts used for degrading printing and dyeing wastewater have low catalytic activity, are easily deactivated, and lose activity in lightless conditions, leading to photocorrosion and structural damage.
A Ag/dual-ligand Sn-MOF composite material is prepared using aromatic carboxylic acid and alkyl imidazole ligands, with Ag nanoparticles loaded via photodeposition, forming a heterostructure that enhances charge transfer and electron storage, maintaining catalytic activity under light and dark conditions.
The composite material exhibits high photocatalytic activity and stability, enabling continuous degradation of organic pollutants in wastewater, including printing and dyeing wastewater, with improved adsorption and degradation efficiency.
Smart Images

Figure CN119175111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic material preparation, and in particular to an Ag / double-ligand Sn-MOF composite material and a preparation method and application thereof. Background Art
[0002] Printing and dyeing wastewater is not only dark in color and has a high chemical oxygen demand, but also contains a large amount of toxic and harmful substances. It is difficult to achieve ideal treatment effects through conventional treatment methods. Photocatalytic technology is a type of advanced oxidation process. It generates electron-hole pairs through photocatalysts excited by light, which in turn generate hydroxyl radicals (·OH) and superoxide radicals (·O2 - ) and other active groups. These active groups come into contact with organic pollutants in the water, causing the organic pollutants to be oxidized and degraded into CO2 and H2O, thereby achieving harmless treatment of organic wastewater. Photocatalytic technology has developed rapidly due to its ability to convert solar energy into chemical energy, and has broad application prospects in the treatment of difficult-to-degrade printing and dyeing wastewater. However, once the light stops (such as at night), the generation of photogenerated carriers in the photocatalyst will immediately stop, and the separation of electron-hole pairs will stop, resulting in the immediate disappearance of catalytic activity, which is also a bottleneck factor restricting the development of photocatalytic technology.
[0003] Metal-Organic Frameworks (MOFs) are a class of porous crystalline solid materials formed by self-assembly of metal ions or metal clusters and organic ligands. MOFs have the characteristics of high specific surface area, multiple active sites, tailorable structure and easy functionalization, which have attracted widespread attention in the field of photocatalysis.
[0004] However, single MOFs materials have disadvantages such as low chemical stability, limited thermal stability and catalytic properties in the aqueous phase. When used in the environmental field, their environmental sensitivity and chemical stability must be considered. At the same time, MOFs materials also have the disadvantage of being deactivated in a lightless environment, and some MOFs materials are prone to photocorrosion or structural damage during the photocatalytic process, resulting in a decrease in photocatalytic performance. Therefore, it is necessary to develop a photocatalytic material with excellent catalytic activity and photocatalytic stability, which can effectively catalyze the degradation of organic matter under lightless conditions, to provide a new solution for the efficient and environmentally friendly treatment of printing and dyeing wastewater. Summary of the invention
[0005] In view of the problems that the photocatalysts for degrading printing and dyeing wastewater in the prior art have low catalytic activity, are easy to deactivate, and the catalytic activity immediately disappears under lightless conditions, the present invention provides an Ag / dual-ligand Sn-MOF composite material and its preparation method and application. The present invention uses aromatic carboxylic acid ligands and alkyl imidazole ligands as organic ligands to prepare a dual-ligand Sn-MOF material, and loads Ag on the dual-ligand Sn-MOF material by photodeposition to form a photocatalytic material with memory catalytic function, which provides an excellent catalyst for industrial treatment of printing and dyeing wastewater and has high promotion and application value.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a Ag / dual ligand Sn-MOF composite material, the preparation method comprising the following steps: S1, dissolving a dual organic ligand in an organic solvent to obtain a ligand solution; the dual organic ligand comprises an aromatic carboxylic acid ligand and an alkyl imidazole ligand; S2, adding a soluble tin salt to the ligand solution, mixing evenly, performing a hydrothermal reaction at 120° C. to 180° C., washing, and drying to obtain a Sn-MOF material; S3, dispersing the Sn-MOF material in a silver salt solution, adding an alcohol solvent, and depositing silver nanoparticles on the surface of the Sn-MOF material using a photoreduction method to obtain an Ag / dual ligand Sn-MOF composite material.
[0007] Compared with the prior art, the preparation method of the Ag / double ligand Sn-MOF composite material provided by the present invention is based on Sn 2+ With aromatic carboxylic acid ligands and alkyl imidazole ligands as metal active centers, a dual-ligand Sn-MOF material with excellent adsorption characteristics, high stability and high photocatalytic activity was prepared by a solvothermal method. At the same time, Ag nanoparticles were loaded onto the dual-ligand Sn-MOF material by photodeposition, which not only increased the specific surface area of the material and provided more reaction active sites, but also the formation of the Ag / Sn-MOF heterostructure reduced the recombination of electron-hole pairs, significantly improved the charge transfer efficiency, and further improved the photocatalytic performance of the composite material. In addition, the heterojunction formed between Ag and the dual-ligand Sn-MOF material can effectively enrich and store photogenerated electrons, and release photogenerated electrons in a dark environment, thereby facilitating the realization of continuous degradation reactions under light and dark conditions.
[0008] Sn can form strong coordination bonds with aromatic carboxylic acid ligands to form a rigid, interconnected framework structure. Using Sn as the metal active center can significantly improve the chemical stability of MOFs materials in water environments. However, the deprotonation degree of aromatic carboxylic acid single-ligand MOFs materials is low, resulting in an insufficient number of active sites in the material, and insufficient stability, reaction selectivity and adsorption performance of the material. Therefore, the present invention utilizes alkyl imidazole ligands as competitive ligands to bridge the deprotonated aromatic carboxylic acid ligands, regulate the structure and morphology of the material, increase the specific surface area of the material, provide more active sites and catalytic substrate / product transmission channels; at the same time, it can also promote the nucleation and growth of crystals to form a crystalline ordered structure, thereby reducing the recombination of photogenerated electrons and holes and improving the photocatalytic efficiency. In addition, using Ag as a dopant can help improve the separation efficiency of photogenerated carriers, and Ag itself can act as an electron trap to capture photogenerated electrons and has electron storage capacity. It works synergistically with the dual-ligand Sn-MOF material to further improve the enrichment and storage of photogenerated electrons. Therefore, the doping of Ag not only improves the photocatalytic activity of the dual-ligand Sn-MOF, but also achieves the purpose of releasing photogenerated electrons in a dark environment and continuously degrading organic pollutants.
[0009] Furthermore, the aromatic carboxylic acid ligand is terephthalic acid, phthalic acid, isophthalic acid or trimesic acid.
[0010] Preferably, the aromatic carboxylic acid ligand is terephthalic acid.
[0011] Furthermore, the alkyl imidazole ligand is 2-methyl imidazole, 4-methyl imidazole, 1,2-dimethyl imidazole or 2,4-dimethyl imidazole.
[0012] Preferably, the alkyl imidazole ligand is 2-methyl imidazole.
[0013] The type of ligand plays a vital role in the structure of MOFs materials and has a significant impact on the photocatalytic activity. The present invention uses aromatic carboxylic acid ligands and alkyl imidazole ligands as dual ligands of MOFs materials, which can effectively improve the specific surface area and porosity of MOFs materials and increase the active sites of MOFs materials. At the same time, aromatic carboxylic acid ligands and alkyl imidazole ligands can promote the transfer of electrons from ligands to metal centers through the metal-ligand charge transfer process, thereby improving the separation efficiency of photogenerated electrons. In addition, the preferred ligands can also improve the water stability of MOFs materials, solving the defects of high environmental sensitivity and low chemical stability of existing MOFs materials.
[0014] Furthermore, the molar ratio of the aromatic carboxylic acid ligand to the alkyl imidazole ligand is 1:0.5-1:3.
[0015] The preferred ligand ratio is beneficial to improving the photocatalytic activity and chemical stability of Sn-MOF materials.
[0016] Furthermore, the concentration of the aromatic carboxylic acid ligand in the ligand solution is 20 mmol / L to 60 mmol / L.
[0017] Preferably, the concentration of the aromatic carboxylic acid ligand in the ligand solution is 20 mmol / L to 40 mmol / L.
[0018] Furthermore, in S1, the organic solvent is a mixed solution of N,N-dimethylformamide and anhydrous ethanol in a volume ratio of 1:2 to 1:4.
[0019] Preferably, in S1, the organic solvent is a mixed solution of N,N-dimethylformamide and anhydrous ethanol in a volume ratio of 1:2.5 to 1:3.5.
[0020] The preferred organic solvent can fully dissolve the organic ligand and the soluble tin salt, thereby facilitating a full reaction of the two during the subsequent hydrothermal reaction.
[0021] Furthermore, in S2, the soluble tin salt is stannous chloride or stannous sulfate.
[0022] Preferably, in S2, the soluble tin salt is stannous chloride.
[0023] Furthermore, the molar ratio of the soluble tin salt to the total amount of the biorganic ligand is 1:0.5 to 1:2.
[0024] Preferably, the molar ratio of the soluble tin salt to the total amount of the biorganic ligand is 1:0.8 to 1:1.5.
[0025] The preferred ratio of soluble tin salt to dual organic ligand is beneficial to improving the photocatalytic activity of Sn-MOF materials.
[0026] Furthermore, in S2, the hydrothermal reaction time is 8h~15h.
[0027] Preferably, in S2, the temperature of the hydrothermal reaction is 140° C. to 160° C., and the time is 10 h to 12 h.
[0028] The optimal reaction temperature and time can improve the crystallinity of Sn-MOF materials, reduce the recombination of photogenerated electrons and holes, and improve the photocatalytic efficiency.
[0029] Furthermore, in S3, the silver salt solution is a silver nitrate aqueous solution with a concentration of 0.20 g / L to 0.30 g / L.
[0030] Preferably, in S3, the silver salt solution is a silver nitrate aqueous solution with a concentration of 0.25 g / L.
[0031] Furthermore, in S3, the mass ratio of the Sn-MOF material to the silver salt in the silver salt solution is 15:1 to 25:1.
[0032] Preferably, in S3, the mass ratio of the Sn-MOF material to the silver salt in the silver salt solution is 18:1 to 22:1.
[0033] The preferred Ag doping amount can further improve the photocatalytic activity of the Sn-MOFs material, as well as the ability of the Sn-MOFs material to enrich and store photogenerated electrons, and increase the reaction duration in a dark environment.
[0034] Furthermore, in S3, a xenon lamp is used to perform photoreduction deposition of silver nanoparticles, the power of the xenon lamp is 300W-500W, and the illumination time is 1h-2h.
[0035] Furthermore, in S3, the alcohol solvent is methanol.
[0036] Furthermore, in S3, after the photo-deposition reaction of silver nanoparticles is completed, the solid and liquid are separated, and the obtained solid is washed with deionized water, dried, and ground to obtain an Ag / dual ligand Sn-MOF composite material.
[0037] Exemplarily, in S3, an optical reactor is used to deposit Ag nanoparticles.
[0038] The present invention also provides an Ag / dual ligand Sn-MOF composite material, which is prepared by any of the above-mentioned methods for preparing the Ag / dual ligand Sn-MOF composite material.
[0039] The Ag / dual-ligand Sn-MOF composite material provided by the present invention has excellent photocatalytic activity and high chemical stability, can maintain activity for a long time under lightless conditions, can achieve continuous degradation of pollutants under light and dark conditions, and provides a catalyst with excellent performance for industrial treatment of organic pollutant wastewater, which has high practical value.
[0040] The present invention also provides the use of the Ag / dual ligand Sn-MOF composite material in degrading organic pollutants in wastewater.
[0041] Furthermore, the wastewater is printing and dyeing wastewater.
[0042] Furthermore, when degrading printing and dyeing wastewater, the concentration of Ag / double ligand Sn-MOF composite material is 1g / L~3g / L, and the concentration of organic pollutants in the printing and dyeing wastewater is 10mg / L~100mg / L.
[0043] Compared with traditional MOF materials, the Ag / dual ligand Sn-MOF composite material provided by the present invention has significantly improved adsorption and degradation efficiency of organic matter. Unlike ordinary doping materials, it has good structural stability and can be recycled. At the same time, it also has a high continuous catalytic degradation efficiency in a dark environment, and has more advantages in degrading organic pollutants, especially printing and dyeing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The scanning electron microscope (SEM) images of the Sn-PTA-MI and Ag / Sn-PTA-MI composite materials prepared in Example 1; wherein, (a) Sn-PTA-MI, (b) Ag / Sn-PTA-MI composite materials; Figure 2 This is the EDX spectrum of the Ag / Sn-PTA-MI composite material prepared in Example 1; wherein the illustration in the upper right corner is the element mass percentage and atomic percentage of each element in the Ag / Sn-PTA-MI composite material; Figure 3 Transmission electron microscopy images of the Ag / Sn-PTA-MI composite material prepared in Example 1, (a) TEM, (b) HRTEM; Figure 4 X-ray diffraction (XRD) patterns of Sn-PTA-MI and Ag / Sn-PTA-MI composite materials prepared in Example 1; Figure 5 The infrared diffraction (FTIR) diagrams of the Sn-PTA-MI and Ag / Sn-PTA-MI composite materials prepared in Example 1; Figure 6 This is the X-ray photoelectron (XPS) image of the Ag / Sn-PTA-MI composite material prepared in Example 1; wherein, (a) full spectrum, (b) Sn 3d, (c) C1s, (d) N 1s, (e) O 1s, (f) Ag 3d; Figure 7 N2 adsorption-desorption curves of Sn-PTA-MI and Ag / Sn-PTA-MI composite materials prepared in Example 1; the inset is the pore size distribution diagram of Sn-PTA-MI and Ag / Sn-PTA-MI composite materials; Figure 8 The electrochemical impedance spectroscopy (EIS) graphs of the Sn-PTA-MI and Ag / Sn-PTA-MI composite materials prepared in Example 1; Fig. 9 To change the effect of the illumination time during the photodeposition of Ag nanoparticles in step S3 of Example 1 on the absorbance of the Ag / Sn-PTA-MI composite material; Fig.10It is a comparison chart of the catalytic effects of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI materials under photocatalysis in Example 1; Fig.11 It is a comparison chart of the catalytic effects of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI materials in Example 1 under dark environment; gray represents the dark reaction stage; Fig.12 It is a comparison chart of the catalytic effects of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI materials in Example 1 under light-dark alternating environments; Fig.13 This is a comparison chart of the catalytic effects of the Ag / Sn-PTA-MI composite material prepared in Example 1 after five cycles of use; Fig.14 This is a three-dimensional fluorescence spectrum of the Ag / Sn-PTA-MI composite material prepared in Example 1; where (a) is MO solution, (b) is dark reaction, (c) is photocatalytic reaction, and (d) is light-dark alternating reaction. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] In order to better illustrate the present invention, further examples are given below.
[0047] Example 1 The present invention provides a method for preparing a Ag / dual-ligand Sn-MOF composite material, comprising the following steps: Step 1: Weigh 2.5 mmol of terephthalic acid (PTA) and 2.5 mmol of 2-methylimidazole (2-MI) and dissolve them in a mixed solution of 20 mL of N,N-dimethylformamide and 60 mL of anhydrous ethanol, and stir for 15 minutes to obtain a ligand solution; Step 2: Weigh 5 mmol SnCl2·2H2O and pour it into the above ligand solution, stir for 15 min, transfer to a hydrothermal reactor, react at 150°C for 12 h, filter, wash the precipitate with ultrapure water and anhydrous ethanol alternately for 3 times, dry at 60°C, and grind to obtain Sn-PTA-MI; Step 3: Weigh 0.1g of the Sn-PTA-MI prepared above and ultrasonically disperse it in 20mL of 0.25g / L AgNO3 aqueous solution. After stirring for 15min, add 0.5mL of methanol and put it into a photochemical reactor. Turn on the xenon lamp, set the power to 400W, irradiate for 2h, filter, wash the solid precipitate with deionized water, dry, and grind to obtain Ag / Sn-PTA-MI composite material.
[0048] Characterization of catalysts: The SEM image of the Ag / Sn-PTA-MI composite material prepared in this example is shown in Figure 1 As shown in (a), the Sn-PTA-MI material has micro-spherical and some block structures. The Ag / Sn-PTA-MI composite material after the deposition of Ag nanoparticles ( Figure 1 (b) shows a fluffy and uneven particle structure. In addition, the blocky particles on the surface of the material are reduced. Figure 2 The EDX spectrum of the Ag / Sn-PTA-MI composite material in Figure 3 proves that Ag was successfully deposited on the Sn-PTA-MI material.
[0049] The TEM image of the Ag / Sn-PTA-MI composite material prepared in this example is shown in Figure 3 As shown, from Figure 3 As can be seen in (a), dark black Ag nanoparticles are sparsely distributed on the surface of Sn-PTA-MI material, with almost no agglomeration. Figure 3 In (b), obvious lattice fringes with a lattice spacing of 0.23 nm can be observed, which corresponds to the (111) crystal plane of Ag nanoparticles (JCPDS No. 01-071-3762); the lattice fringes with a lattice spacing of 0.26 nm correspond to the (101) crystal plane of SnO2 (JCPDS No. 46-1088), which is consistent with the observations of the XRD spectrum, once again proving that the Ag nanoparticles are effectively dispersed on the Sn-PTA-MI surface.
[0050] The XRD pattern of the Ag / Sn-PTA-MI composite material prepared in this example is shown in Figure 4As shown in the figure, it can be seen that the crystal structure of Ag / Sn-PTA-MI is mainly composed of (121) and (017) crystal planes of C3H7NO6Sn (PDF#19-0074) at 2θ=29.6° and 37.1°, and (110), (101) and (211) crystal planes of SnO2 (JCPDS No. 46-1088) at 2θ=26.6°, 33.8° and 51.8°. The broadening of the diffraction peak range of the (110) crystal plane at 2θ=26.6° is attributed to the influence of some impurity peaks. It is worth noting that due to the low content of Ag in the catalyst, the characteristic diffraction peaks of Ag are not shown in the XRD spectrum of Ag / Sn-PTA-MI.
[0051] The FTIR image of the Ag / Sn-PTA-MI composite material prepared in this example is as follows: Figure 5 As shown in the figure, Sn-PTA-MI and Ag / Sn-PTA-MI show very similar characteristics in bonding vibration. -1 The characteristic peak of -OH group appeared at 2340 cm -1 The C≡N band signal at 1600 cm-1 was covered by the Ag loading. Sn-PTA-MI and Ag / Sn-PTA-MI both showed a C≡N band at 1600 cm-1. -1 and 1340 cm -1 The bands on the left and right correspond to COO - Symmetric stretching vibration characteristic peaks and asymmetric stretching characteristic peaks. -1 The Sn-PTA-MI and Ag / Sn-PTA-MI on the left and right both show the characteristic peaks of Sn-O stretching vibration. It is worth noting that Ag is a material that is easily affected by oxygen. However, in the FT-IR spectrum, there is no characteristic peak of the Ag-O bond, which indicates that Ag remains stable after being loaded on Sn-PTA-MI and will not be oxidized due to environmental conditions. Similar to the above XRD results, no abnormal crystalline phase structure related to Ag was found.
[0052] The XPS graph of the Ag / Sn-PTA-MI composite material prepared in this example is as follows: Figure 6 As shown, Figure 6 As shown in (a), Sn, C, N, O, and Ag elements appear in the element spectrum of the sample, proving the existence of these elements in the sample and revealing the formation of the heterogeneous structure of Ag nanoparticles and Sn-PTA-MI. Figure 6As shown in (b), the characteristic peaks of Sn at 487.1 eV and 495.5 eV binding energies are attributed to Sn 3d5 / 2 and Sn 3d3 / 2 orbitals, which indicates that there is Sn 4+ Existing in Ag / Sn-PTA-MI. In the C 1s spectrum ( Figure 6 (c)), the characteristic peaks at 284.8 eV, 286.0 eV and 288.9 eV correspond to CC, CO and OC=O bonds. Figure 6 The peak at 400.7 eV in (d) can be attributed to the NC bond brought by the imidazole ring in the 2-MI ligand. Figure 6 (e)), the characteristic peaks at 530.9 eV and 531.6 eV correspond to -OH and C=O bonds, respectively. Figure 6 (f)), the peaks at 367.9 eV and 374.0 eV correspond to metallic Ag, proving that AgNO3 reduces metallic Ag and deposits on the catalyst by storing photogenerated electrons, which is beneficial for the subsequent release of electrons in the dark reaction to continue the catalytic reaction.
[0053] The BET specific surface area, pore size and pore volume of the Sn-PTA-MI and Ag / Sn-PTA-MI samples prepared in this example were tested using nitrogen adsorption-desorption isotherms. Figure 7 As shown in the figure, both Sn-PTA-MI and Ag / Sn-PTA-MI present a type IV isotherm H4 hysteresis loop, indicating that there are narrow pores in the material, which is conducive to the exposure of active sites. As can be seen from the illustration, the pore size distribution of both is mainly concentrated in 1 nm~5 nm, and the pore structure is mainly composed of micropores and mesopores.
[0054] The results of sample specific surface area, pore volume and pore size are shown in Table 1. After the introduction of Ag, the specific surface area and pore volume of Ag / Sn-PTA-MI are greatly improved compared with Sn-PTA-MI. This means that Ag / Sn-PTA-MI can provide more reaction sites for the contact between the catalyst and the pollutant, which is beneficial to improve the catalytic activity. However, the pore size of Ag / Sn-PTA-MI is smaller than that of Sn-PTA-MI. This is because Ag nanoparticles fill some larger pores, thereby reducing the pore size of Ag / Sn-PTA-MI. The peak of the pore size distribution of Ag / Sn-PTA-MI in the illustration moves to smaller nanometers for this reason.
[0055] Table 1 Specific surface area, pore volume and pore diameter of samples
[0056] The EIS graphs of Sn-PTA-MI and Ag / Sn-PTA-MI prepared in this example are shown in Figure 2. Figure 8 As shown in the figure, it can be seen that the radius of the semicircular EIS Nyquist plot of Ag / Sn-PTA-MI is smaller than that of Sn-PTA-MI, which means that the charge transfer resistance at the electrode interface of the Ag / Sn-PTA-MI sample is smaller than that of Sn-PTA-MI, which also reflects that Ag / Sn-PTA-MI has a high charge transfer rate, better photogenerated electron-hole pair separation effect, and better catalytic activity.
[0057] AgNO3, as an electron scavenger, can capture photoelectrons for Ag reduction, and capture and store more photoelectrons as the light excitation time increases. Fig. 9 The effect of illumination time on the photodeposition of Ag by Sn-PTA-MI was studied. The specific experimental process is as follows: 0.1 g of the Sn-PTA-MI material prepared in Example 1 was ultrasonically dispersed in 20 mL of 0.25 g / L AgNO3 solution. The mixture was stirred for 15 min, 0.5 mL of methanol was added, and the mixture was placed in a photochemical reactor. A 500 W xenon lamp was turned on for illumination. Samples were taken at different time intervals (0 min, 30 min, 60 min, 90 min, 120 min, 150 min), and then a full wavelength scan was performed.
[0058] When Ag ions receive photogenerated electrons generated by Sn-PTA-MI, the electron-induced silver plasmon band (the fluctuating electromagnetic oscillation of the metal coupled charge at the dielectric interface) stored in the reduced Ag nanoparticles can be observed in the range of 350~550nm in the UV-visible absorption spectrum. It can be seen that with the increase of illumination time, the absorption band shifts up, which is related to the accumulation of electrons in Ag. However, after the illumination time is extended to 150min, the absorption band shifts down, which is attributed to the fact that the electrons stored in Ag are captured by AgNO3 in the solution. This phenomenon provides strong evidence that Ag nanoparticles can store photogenerated electrons.
[0059] Example 2 The present invention provides a method for preparing a Ag / dual-ligand Sn-MOF composite material, comprising the following steps: Step 1: Weigh 2.5 mmol of phthalic acid (PA) and 0.5 mmol of 4-methylimidazole (4-MI) and dissolve them in a mixed solution of 25 mL of N,N-dimethylformamide and 100 mL of anhydrous ethanol, and stir for 15 minutes to obtain a ligand solution; Step 2: Weigh 6 mmol SnCl2·2H2O and pour it into the above ligand solution, stir for 15 min, transfer to a hydrothermal reactor, react at 150°C for 12 h, filter, wash the precipitate with ultrapure water and anhydrous ethanol alternately for 3 times, dry at 60°C, and grind to obtain Sn-PA-MI; Step 3: Weigh 0.06 g of the Sn-PA-MI prepared above and ultrasonically disperse it in 20 mL of 0.2 g / L AgNO3 aqueous solution. After stirring for 15 min, add 0.5 mL of methanol and put it into a photochemical reactor. Turn on the xenon lamp, set the power to 500 W, irradiate for 1 h, filter, wash the solid precipitate with deionized water, dry, and grind to obtain an Ag / Sn-PA-MI composite material.
[0060] Example 3 The present invention provides a method for preparing a Ag / dual-ligand Sn-MOF composite material, comprising the following steps: Step 1: Weigh 2.5 mmol of trimesic acid (H3BTC) and 7.5 mmol of 1,2-dimethylimidazole (1,2-MI) and dissolve them in a mixed solution of 14 mL of N,N-dimethylformamide and 28 mL of anhydrous ethanol, and stir for 15 minutes to obtain a ligand solution; Step 2: Weigh 5 mmol SnCl2·2H2O and pour it into the above ligand solution, stir for 15 min, transfer to a hydrothermal reactor, react at 150°C for 12 h, filter, wash the precipitate with ultrapure water and anhydrous ethanol alternately for 3 times, dry at 60°C, and grind to obtain Sn-H3BTC-MI; Step 3: Weigh 0.15 g of the Sn-H3BTC-MI prepared above and ultrasonically disperse it in 20 mL of 0.3 g / L AgNO3 aqueous solution. After stirring for 15 min, add 0.5 mL of methanol and put it into a photochemical reactor. Turn on the xenon lamp, set the power to 300 W, irradiate for 2 h, filter, wash the solid precipitate with deionized water, dry, and grind to obtain Ag / Sn-H3BTC-MI composite material.
[0061] Comparative Example 1 This comparative example provides a method for preparing a Ag / Sn-PTA photocatalytic material, comprising the following steps: Step 1: Weigh 2.5 mmol of terephthalic acid (PTA) and dissolve it in a mixed solution of 20 mL of N,N-dimethylformamide and 60 mL of anhydrous ethanol, and stir for 15 minutes to obtain a ligand solution; Step 2: Weigh 5 mmol SnCl2·2H2O and pour it into the above ligand solution, stir for 15 min, transfer to a hydrothermal reactor, react at 150°C for 12 h, filter, wash the precipitate with ultrapure water and anhydrous ethanol alternately for 3 times, dry at 60°C, and grind to obtain Sn-PTA; Step 3: Weigh 0.1g of the Sn-PTA prepared above and ultrasonically disperse it in 20mL of 0.25g / L AgNO3 aqueous solution. After stirring for 15min, add 0.5mL of methanol and put it into a photochemical reactor. Turn on the xenon lamp, set the power to 400W, irradiate for 2h, filter, wash the solid precipitate with deionized water, dry, and grind to obtain an Ag / Sn-PTA composite material.
[0062] Comparative Example 2 This comparative example provides a method for preparing a Sn-MI catalytic material, comprising the following steps: Step 1: Weigh 2.5 mmol of 2-methylimidazole (2-MI) and dissolve it in a mixed solution of 20 mL of N,N-dimethylformamide and 60 mL of anhydrous ethanol, and stir for 15 minutes to obtain a ligand solution; Step 2: Weigh 5 mmol SnCl2·2H2O and pour it into the above ligand solution, stir for 15 min, transfer to a hydrothermal reactor, react at 150°C for 12 h, filter, wash the precipitate with ultrapure water and anhydrous ethanol alternately for 3 times, dry at 60°C, and grind to obtain Sn-MI; Step 3: Weigh 0.1g of the Sn-PTA prepared above and ultrasonically disperse it in 20mL of 0.25g / L AgNO3 aqueous solution. After stirring for 15min, add 0.5mL of methanol and put it into a photochemical reactor. Turn on the xenon lamp, set the power to 400W, irradiate for 2h, filter, wash the solid precipitate with deionized water, dry, and grind to obtain Ag / Sn-MI composite material.
[0063] Photocatalytic performance test 1. Under lighting conditions Weigh 0.1g of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI prepared in Example 1 and Comparative Examples 1 to 2, respectively, add them to 50 mL of methyl orange (MO) solution with a concentration of 20 mg / L, place them in a photochemical reactor with condensed water, and conduct photocatalytic experiments at room temperature. The mixing and stirring speed is 200 r / min. After stirring in a dark environment for 15 minutes, turn on a 500 W xenon lamp to start the photocatalytic experiment. Take water samples every 15 minutes, filter the water samples, and measure the absorbance at a wavelength of 463 nm using a UV-visible spectrophotometer. The results are as follows: Fig.10 And as shown in Table 2.
[0064] Table 2 Removal rate of MO under light conditions
[0065] Under the conditions of light reaction, the photocatalytic degradation of MO by Sn-PTA-MI is better than that of single-ligand MOF materials Sn-PTA and Sn-MI. After the Ag element is deposited on Sn-PTA, Sn-MI, and Sn-PTA-MI materials, the photocatalytic effect of the composite materials is better than that of the single MOF material, among which Ag / Sn-PTA-MI removes 91.77% of MO after 60 minutes of illumination.
[0066] 2. Dark reaction Weigh 0.1g of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI prepared in Example 1 and Comparative Examples 1 to 2, turn on a 500W xenon lamp for 2h, add them to 50mL of methyl orange (MO) solution with a concentration of 20mg / L, place them in a photochemical reactor with condensed water, do not turn on the xenon lamp, and conduct dark reaction experiments at room temperature with a mixing and stirring speed of 200 r / min. Take water samples every 15 minutes, filter the water samples, and measure the absorbance at a wavelength of 463nm using a UV-visible spectrophotometer. The results are as follows: Fig.11 And as shown in Table 3.
[0067] Table 3 Removal rate of MO under dark reaction conditions
[0068] After the catalyst was excited by light for 2 hours, it degraded MO solution under dark reaction conditions. The degradation of pollutants by Sn-PTA, Sn-MI and Sn-PTA-MI was mainly due to adsorption. After 30 minutes, the pollutants were basically no longer reduced. However, Ag / Sn-PTA, Ag / Sn-MI and Ag / Sn-PTA-MI all had a continuous degradation effect on pollutants under dark reaction conditions. Among them, Ag / Sn-PTA-MI could achieve a pollutant removal effect of 41.75% after 60 minutes under dark reaction conditions, which was 11% higher than that of Sn-PTA-MI. These indicate that the Ag element can form a heterostructure with MOF under light conditions, avoid hole-electron recombination, and improve the photocatalytic effect; on the other hand, it can act as an electron trap to capture photogenerated electrons for electron storage, and release electrons under dark reaction to achieve continuous degradation of pollutants.
[0069] 3. Light-dark reaction Weigh 0.1g of Sn-PTA, Sn-MI, Sn-PTA-MI, Ag / Sn-PTA, Ag / Sn-MI, and Ag / Sn-PTA-MI prepared in Example 1 and Comparative Examples 1 to 2, turn on a 500W xenon lamp for 2h, add them to 50mL of methyl orange (MO) solution with a concentration of 20mg / L, place them in a photochemical reactor with condensed water, and perform light-dark alternation reaction experiments at room temperature. The mixing and stirring speed is 200 r / min. First, turn on the 500W xenon lamp for 15min of light reaction, then turn off the xenon lamp for 15min of dark reaction. Perform light-dark alternation every 15min, and take water samples every 15min. After filtering, use a UV-visible spectrophotometer to measure the absorbance at a wavelength of 463nm. The results are as follows Fig.12 And as shown in Table 4.
[0070] Table 4 Removal rate of MO under light-dark alternation conditions
[0071] After the catalyst was excited by light for 2 hours, it carried out the light-dark alternating catalytic reaction. Ag / Sn-PTA, Ag / Sn-MI and Ag / Sn-PTA-MI could achieve continuous degradation of pollutants under light and dark conditions; but Sn-PTA, Sn-MI and Sn-PTA-MI could only catalytically degrade pollutants under light conditions. Among them, Ag / Sn-PTA-MI had the best catalytic effect. After 45 minutes of reaction under light-dark alternating conditions, the pollutants could be degraded by more than 99%, which can greatly reduce energy consumption in practical applications.
[0072] 4. Cycle performance After the light-dark alternating reaction test, the Ag / Sn-PTA-MI catalyst was recovered by centrifugation. The used catalyst was washed three times with ethanol and deionized water alternately, dried at 60°C, and ground for later use. The above light-dark alternating reaction process was repeated 5 times. The results of MO removal efficiency are shown in Fig.13 And as shown in Table 5.
[0073] Table 5 Cycle performance data
[0074] 5. Three-dimensional fluorescence test of water samples Preparation of test samples: (a) MO solution: prepare 20 mg / L methyl orange (MO) solution and take 3 mL of the prepared MO solution for testing; (b) Dark reaction: 0.1 g of the Ag / Sn-PTA-MI catalyst prepared in Example 1 was placed in a photochemical reactor, and a 500 W xenon lamp was turned on for 2 h. Then, the catalyst was placed in 50 mL of MO solution, and the xenon lamp was turned off. The reaction was carried out in the absence of light for 60 min, and then 3 mL of the catalyst was sampled for testing. (c) Photocatalytic reaction: 0.1 g of the Ag / Sn-PTA-MI catalyst prepared in Example 1 was added to 50 mL of MO solution, placed in a photocatalytic reactor, and a 500 W xenon lamp was turned on. The reaction was allowed to proceed under photocatalytic conditions for 60 min, and then 3 mL of the sample was taken for testing; (d) Light-dark alternating reaction: 0.1 g of the Ag / Sn-PTA-MI catalyst prepared in Example 1 was added to 50 mL of MO solution, placed in a photocatalytic reactor, and a 500 W xenon lamp was turned on. The light-dark catalytic reaction was performed alternately every 15 min. After 60 min, 3 mL of the sample was taken for testing.
[0075] Turn on the synchronous absorption-3D fluorescence spectrometer and preheat for 20 min. Open the measurement software, rinse the quartz cuvette with distilled water, take 3 mL of each sample solution and place it in the cuvette, and put it into the sample pool. The spectral range of this instrument is 230 nm~800nm. Set the initial measurement spectrum to 230 nm, excitation bandwidth 5 nm, emission bandwidth 5 nm, and grating 1800 g / mm@400nm. Ensure that the sample is fully exposed to the excitation light. Start the measurement program and record the fluorescence spectrum data. The results are as follows: Fig.14 shown.
[0076] like Fig.14 As shown in (a), the original MO solution does not appear in the effective excitation and emission wavelengths of the three-dimensional fluorescence spectrum. Fig.14 (b) After 60 minutes of the Ag / Sn-PTA-MI dark reaction experiment to degrade MO, a fluorescence peak appeared in the IV region of the water sample, which was attributed to the oxidative degradation reaction caused by the release of electrons stored in the Ag / Sn-PTA-MI pre-illumination process. Fig.14 (c) After 60 min of the light reaction experiment, two main fluorescence peaks appeared in the water sample detection in all five partitions, indicating that MO was catalytically degraded into more biodegradable small molecules. Fig.14 (d) shows the degradation products after light-dark reaction. A fluorescence peak with obvious fluorescence intensity is formed in the four partitions, indicating that MO is also degraded into small molecular products under the light-dark reaction conditions.
[0077] The Ag / dual-ligand Sn-MOF materials prepared by using other ligands defined in the present invention can achieve effects substantially equivalent to those of Example 1.
[0078] In summary, Ag / Sn-PTA-MI can be excited by light and continuously catalytically degrade pollutants into small molecules that can be biochemically treated in a lightless environment. Memory catalysis is fundamentally based on the reaction of electrons and O2 to produce active components to redox pollutants. The stored electrons may also combine with other electron acceptors, thus affecting the effect of pollutant degradation.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Ag / dual ligand Sn-MOF composite material, characterized in that: The steps include: S1, dissolving a dual organic ligand in an organic solvent to obtain a ligand solution; the dual organic ligand comprises an aromatic carboxylic acid ligand and an alkyl imidazole ligand; S2, adding a soluble tin salt to the ligand solution, mixing evenly, performing a hydrothermal reaction at 120° C. to 180° C., washing, and drying to obtain a Sn-MOF material; S3, dispersing the Sn-MOF material in a silver salt solution, adding an alcohol solvent, and depositing silver nanoparticles on the surface of the Sn-MOF material using a photoreduction method to obtain an Ag / dual ligand Sn-MOF composite material.
2. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1, characterized in that: The aromatic carboxylic acid ligand is terephthalic acid, phthalic acid, isophthalic acid or trimesic acid; and / or The alkylimidazole ligand is 2-methylimidazole, 4-methylimidazole, 1,2-dimethylimidazole or 2,4-dimethylimidazole.
3. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1 or 2, characterized in that: The molar ratio of the aromatic carboxylic acid ligand to the alkyl imidazole ligand is 1:0.5 to 1:3; and / or The concentration of the aromatic carboxylic acid ligand in the ligand solution is 20 mmol / L to 60 mmol / L.
4. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1, characterized in that: In S1, the organic solvent is a mixed solution of N,N-dimethylformamide and anhydrous ethanol in a volume ratio of 1:2 to 1:
4.
5. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1, characterized in that: In S2, the soluble tin salt is stannous chloride or stannous sulfate.
6. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1 or 5, characterized in that: The molar ratio of the soluble tin salt to the total amount of the biorganic ligand is 1:0.5 to 1:
2.
7. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1, characterized in that: In S2, the hydrothermal reaction time is 8h~15h.
8. The method for preparing the Ag / dual ligand Sn-MOF composite material according to claim 1, characterized in that: In S3, the silver salt solution is an aqueous solution of silver nitrate with a concentration of 0.20 g / L to 0.30 g / L; and / or In S3, the mass ratio of the Sn-MOF material to the silver salt in the silver salt solution is 15:1 to 25:1; and / or In S3, a xenon lamp is used to perform photoreduction deposition of silver nanoparticles, the power of the xenon lamp is 300W-500W, and the illumination time is 1h-2h.
9. An Ag / double-ligand Sn-MOF composite material, characterized in that: The composite material is prepared by the method for preparing the Ag / dual ligand Sn-MOF composite material according to any one of claims 1 to 8.
10. Use of the Ag / dual ligand Sn-MOF composite material according to claim 9 in degrading organic pollutants in wastewater.
Citation Information
Patent Citations
In-situ preparation method of composite photocatalytic material
CN108620131A
Heterojunction MOF (Metallic Organic Framework) catalyst as well as preparation method and application thereof
CN108745418A
Magnetic metal organic framework composite material and preparation method and application thereof
CN111298842A
A composition for the synthesis of Ag-doped CuO and SnO2 nanoparticles
DE202022103529U1
